Corrigendum to “Remote sensing-based assessment of alpha and beta diversity for mapping priority conservation areas in the Yucatán Peninsula” [Remote Sens. Appl.: Soc. Environ. 42 (2026) 102103] - Víctor Alexis Peña-Lara; Juan Manuel Dupuy-Rada; Germán Carnevali Fernández-Concha; Lucía Sanaphre-Villanueva; Diego F. Angulo; José Luis Hernández-Stefanoni (Remote Sensing Applications: Society and Environment, 2026)

Remote sensing-based assessment of alpha and beta diversity for mapping priority conservation areas in the Yucatán Peninsula - Víctor Alexis Peña-Lara; Juan Manuel Dupuy-Rada; Germán Carnevali Fernández-Concha; Lucia Sanaphre-Villanieva; Diego F. Angulo; José Luis Hernández-Stefanoni (Remote Sensing Applications: Society and Environment, 2026)

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Unearthing the soil‐borne microbiome of land plants - Raúl Ochoa‐Hueso; David J. Eldridge; Miguel Berdugo; Pankaj Trivedi; Blessing Sokoya; Concha Cano‐Díaz; Sebastian Abades; Fernando Alfaro; Adebola R. Bamigboye; Felipe Bastida; José L. Blanco‐Pastor; Asunción de los Rios; et al. (Global Change Biology, 2024)
Plant–soil biodiversity interactions are fundamental for the functioning of terrestrial ecosystems. Yet, the existence of a set of globally distributed topsoil microbial and small invertebrate organisms consistently associated with land plants (i.e., their consistent soil‐borne microbiome), together with the environmental preferences and functional capabilities of these organisms, remains unknown. We conducted a standardized field survey under 150 species of land plants, including 58 species of bryophytes and 92 of vascular plants, across 124 locations from all continents. We found that, despite the immense biodiversity of soil organisms, the land plants evaluated only shared a small fraction (less than 1%) of all microbial and invertebrate taxa that were present across contrasting climatic and soil conditions and vegetation types. These consistent taxa were dominated by generalist decomposers and phagotrophs and their presence was positively correlated with the abundance of functional genes linked to mineralization. Finally, we showed that crossing environmental thresholds in aridity (aridity index of 0.65, i.e., the transition from mesic to dry ecosystems), soil pH (5.5; i.e., the transition from acidic to strongly acidic soils), and carbon (less than 2%, the lower limit of fertile soils) can result in drastic disruptions in the associations between land plants and soil organisms, with potential implications for the delivery of soil ecosystem processes under ongoing global environmental change.

Dragon’s Blood: antioxidant properties for nutraceuticals and pharmaceuticals - Isabella S. A. Peres; Kiara A. O. Conceição; Larissa A. F. Silva; Nadia G. Khouri; Cristiana M. P. Yoshida; Viktor O. C. Concha; Massimo Lucarini; Alessandra Durazzo; Antonello Santini; Eliana B. Souto; Patricia Severino (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)
Plants are the source of a large spectrum of phytochemicals, and the combined and concerted action of biologically active compounds lead to the potential beneficial properties of each plant matrix. A great attention is being addressed over the years toward herbs and medicinal plants. Dragon’s Blood is a reddish resin oil extracted from Croton lechleri tree. It has been extensively used by indigenous cultures of the Amazon River since ancient times due to the beneficial nutraceutical and pharmaceutical properties. This perspective aims at providing a current framework on Dragon’s Blood with focus on antioxidant properties for nutraceuticals and pharmaceuticals in a novelty integrated and multidisciplinary manner, highlighting the current knowledge, the main research lines, and emerging strategies. A literature quantitative research analysis approach was applied as starting point. The literature search was carried out by means of the Scopus database; 365 documents have been retrieved in the year range from 1854 to 2021, and a total of 269 terms were identified. Among the top-recurring keywords appear: unclassified drug, nonhuman, plant extract/s, Dragon’s Blood, dracaena, Dragon Blood, chemistry, human, animal/s, plant resin. Source, chemical composition, potential nutraceutical, and therapeutical applications of Dragon’s Blood are discussed here. The anti-inflammatory, wound healing, antidiarrheals, anticancer, antirheumatic, antiseptic, and antioxidant activities identified in the Dragon’s Blood extracts can open novel perspectives for its use in food and pharmaceutical industries. While different bioactive compounds have already been identified in Dragon’s Blood extract, only a few studies can be found in literature.

Descending necrotizing mediastinitis from Ludwig’s angina: a life-threatening condition - Miguel F. Carrascosa; Silvia Cayón Hoyo; Roberto Echeverría San-Sebastián; Iratxe Alcalde Díez; Sergio Tapia Concha; Sandra Campos Fernández; Eva María Alonso-Fernández; Carmen González-Carrero Sixto; David Lobo Duro; Laura Sánchez Moreno; Miguel Ángel Zabaleta-Murguiondo (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Lessons for research, capacity development and policy in agroforestry for development - D. Callo-Concha; M. Denich; M. M. Ul Hassan; F. Place; D. A. Wardell (Agroforestry Systems, 2017)

Active Biomonitoring of Heavy Metals and PAHs with Mosses and Lichens: a Case Study in the Cities of Naples and London - S. Vingiani; F. De Nicola; W. O. Purvis; E. Concha-Graña; S. Muniategui-Lorenzo; P. López-Mahía; S. Giordano; P. Adamo (Water, Air, & Soil Pollution, 2015)

Biomedical application of fuzzy association rules for identifying breast cancer biomarkers - F. J. Lopez; M. Cuadros; C. Cano; A. Concha; A. Blanco (Medical & Biological Engineering & Computing, 2012)

Reproductive biology of Zearaja chilensis (Chondrichthyes: Rajidae) in the south‐east Pacific Ocean - C. Bustamante; C. Vargas‐Caro; M. C. Oddone; F. Concha; H. Flores; J. Lamilla; M. B. Bennett (Journal of Fish Biology, 2012)
Between 2000 and 2002, three artisanal landing sites were sampled in southern Chile, with data on population structure and reproductive development collected from 5477 yellownose skates Zearaja chilensis . Total length ( L T ) ranged from 33 to 158 cm for females and 34 to 155 cm for males. No sexual dimorphism was evident in disc size (length or width) or in L T – mass relationships. The smallest mature female was 95 cm L T and the size at which 50% were mature ( L T50 ) was 109 cm. Males matured between 80 and 90 cm L T with a L T50 of 88 cm. Although the largest Z . chilensis captured by the artisanal fishery was 155 cm L T , 89% of landings comprised relatively small, immature fish. This situation may compromise the stock integrity if intrinsic vulnerability and probable long‐life span of Z . chilensis are considered. Consequences for the survival of the species and possible signs of a fishery collapse must be reviewed by management authorities by consideration of both artisanal and industrial landings in Chile.

Egg capsules of the dusky catshark Bythaelurus canescens (Carcharhiniformes, Scyliorhinidae) from the south‐eastern Pacific Ocean - F. Concha; C. Bustamante; M. C. Oddone; S. Hernández; J. Lamilla (Journal of Fish Biology, 2010)
The external morphology of the egg capsule of Bythaelurus canescens and its fixation to the substratum are described. Bythaelurus canescens egg capsules are typically vase‐shaped, dorso‐ventrally flattened, pale yellow in colour when fresh and covered by 12–15 longitudinal ridges. The anterior border of the capsule is straight, whereas the posterior border is semicircular. Two horns bearing long, coiled tendrils arise from the anterior and posterior ends of the capsule. The presence of longitudinal ridges and long coiled tendrils at both anterior and posterior ends of the capsule readily distinguish these egg capsules from those of other chondrichthyans occurring in the south‐east Pacific Ocean.

Evidence for apparent gene instability in the rifamycin-producing oligoketide synthase. Implications for combinatorial biosynthesis and heterologous gene expression - N. Perić-Concha; G. Castaldo; P. F. Long (Folia Microbiologica, 2005)

Rapid detection of `rare' actinomycetes in environmental samples - Esther W.N. Gathogo; Alastair C.W. Waugh; Nataša Perić-Concha; Maria B. Redpath; Paul F. Long (Biotechnology Letters, 2004)

Construction and characterization of a recombinant ovine lentivirus carrying the optimized green fluorescent protein gene at the dUTPase locus - Z. Zhang; J. Guo; Y. Ni; F. W. Bazer; L. Giavedoni; A. de la Concha-Bermejillo (Archives of Virology, 2003)

Evaluation of the internalization process of the fish pathogen Renibacterium salmoninarum in cultured fish cells - M. González; F. Sánchez; M. I. Concha; J. Figueroa; M. I. Montecinos; G. León (Journal of Fish Diseases, 1999)